MENGEMAS IMPLEMENTASI PENDIDIKAN MORAL DI SEKOLAH - Ahmad Ta'rifin (IAIN Pekalongan, 2011)
Abstract: The school has an urgent function and special mission tocreate moral beings, which are formed according to community needs.Although the family is the most appropriate and effective in generatingand managing the underlying feelings which are simple and be thefoundation of morality, however, the family is not an institution that isfounded with the goal of educating children to be able to meet thedemands of society. At this stage of schools- especially primaryschools - this is the moral education of children began to be given,although the material provided is still common. Conversely, when thestage of primary school age went by without laying the foundationsof morality, that foundations of morality will never be implanted in thechild. In its implementation, the moral education in schools will beeffective if there is any Â«modelÂ» and the consistency of the educators.Attitudes and behaviors of educators, especially honesty, as the mirrorof character is not possible to be camouflaged, because actually, it isa process of delivering the most effective moral values. Therefore,honesty is the base of truth and righteousness which is the essenceof moral values.